Peran bedaquiline untuk tuberkulosis resisten obat: A literature review - Darmanto, Arief Gunawan; Dewi, Desak Nyoman Surya Suameitria (Holistik Jurnal Kesehatan, 2025)
Background: Multidrug-resistant tuberculosis (MDR/RR-TB) is a serious challenge in global TB elimination efforts. Indonesia as a country with a high TB ​​burden faces the problem of MDR/RR-TB therapy, where the effectiveness of second-line treatment is still limited. Bedaquiline, a new drug from the diarylquinoline group, has emerged as a leading candidate in the treatment of MDR/RR-TB with a unique mechanism of action. Purpose: To provide a comprehensive understanding of bedaquiline in the context of its mechanism of action, clinical efficacy, safety profile, development of resistance, and national and global guidelines for its use. Methods: This study is a literature review with reference searches from the PubMed and ScienceDirect databases using the keywords: Tuberculosis, MDR/RR-TB, and Bedaquiline. Articles that met the inclusion criteria were from 2005–2024 and included various types of research, including clinical studies, experiments, and systematic reviews. Results: Bedaquiline has been shown to increase the rate of culture conversion and the success of MDR/XDR-TB therapy. This drug is also recommended by WHO and the Indonesian Ministry of Health in short and long regimens for MDR-TB. However, the risk of side effects such as QT interval prolongation and the emergence of resistance through genetic mutations remain major concerns, so ECG monitoring and genetic resistance testing are essential. Conclusion: Bedaquiline is a major advancement in drug-resistant TB treatment, offering new hope for improving patient outcomes. Nevertheless, its use must be accompanied by careful monitoring of adverse effects and resistance. Suggestion: Further research is needed to identify optimal drug combinations, determine ideal treatment durations, and monitor long-term resistance development to ensure sustained effectiveness of bedaquiline.   Keywords: Bedaquiline; Drug Resistance; Tuberculosis.   Pendahuluan: Tuberkulosis resisten obat (MDR/RR-TB) menjadi tantangan serius dalam upaya eliminasi TB global. Indonesia sebagai negara dengan beban TB tinggi menghadapi permasalahan terapi MDR/RR-TB, di mana efektivitas pengobatan lini kedua masih terbatas. Bedaquiline, obat baru dari golongan diarylquinoline, muncul sebagai kandidat utama dalam pengobatan MDR/RR-TB dengan mekanisme kerja yang unik. Tujuan: Untuk memberikan pemahaman komprehensif tentang bedaquiline dalam konteks mekanisme aksi, efikasi klinis, profil keamanan, perkembangan resistensi, serta pedoman nasional dan global penggunaannya. Metode: Studi literature review dengan pencarian referensi dari database PubMed dan ScienceDirect menggunakan kata kunci Tuberculosis, MDR/RR-TB, dan Bedaquiline. Artikel yang memenuhi kriteria inklusi yaitu yang diterbitkan tahun 2005–2024 dan mencakup berbagai jenis penelitian, termasuk studi klinis, eksperimen, dan tinjauan sistematis. Hasil: Bedaquiline terbukti meningkatkan tingkat konversi kultur dan keberhasilan terapi MDR/XDR-TB. Obat ini juga direkomendasikan oleh WHO dan Kementerian Kesehatan RI dalam rejimen pendek dan panjang untuk MDR-TB. Namun, risiko efek samping seperti pemanjangan interval QT dan munculnya resistensi melalui mutasi genetik tetap menjadi perhatian utama, sehingga pemantauan EKG dan pengujian resistensi genetik sangat diperlukan. Simpulan: Bedaquiline merupakan inovasi penting dalam terapi TB resisten obat, memberikan harapan baru dalam meningkatkan outcome pasien. Namun, penggunaannya harus disertai dengan pemantauan ketat terhadap efek samping dan resistensi. Saran: Diperlukan penelitian lanjutan terkait kombinasi optimal, durasi terapi yang ideal, serta pemantauan jangka panjang terhadap resistensi untuk memastikan efektivitas jangka panjang bedaquiline.   Kata Kunci: Bedaquiline; Resisten Obat; Tuberkulosis.